2003
DOI: 10.1159/000068576
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of TSH in Congenital Hypothyroidism Is Significantly Related to Serum Levels and Dosage of Thyroxine

Abstract: Aim: To assess thyrotropin (thyroid-stimulating hormone; TSH) suppression and serum thyroxine (T4) concentrations in infants with congenital hypothyroidism in relation to T4 dose and pretreatment parameters. Method: A retrospective study of all cases treated in a single centre since neonatal screening began was performed. Results: In 54 infants treated with a mean daily T4 dose of 9.8 µg/kg, the TSH concentration was suppressed (<6 mU/l) in 65% of the cases by 6 months with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Some authors draw blood every 4 to 5 days during the first few weeks of treatment, 30 whereas others sample much less frequently. 31 The schedule recommended by the American Academy of Pediatrics has been evaluated in one study of children treated with 6.6 to 10 lg/kg per day, which did not include IQ as the outcome. 32 We follow the recommendation of Fisher and Foley 9 and wait until at least 4 half-lives of thyroxine have elapsed before taking the first sample on treatment, and then follow the schedule outlined above.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors draw blood every 4 to 5 days during the first few weeks of treatment, 30 whereas others sample much less frequently. 31 The schedule recommended by the American Academy of Pediatrics has been evaluated in one study of children treated with 6.6 to 10 lg/kg per day, which did not include IQ as the outcome. 32 We follow the recommendation of Fisher and Foley 9 and wait until at least 4 half-lives of thyroxine have elapsed before taking the first sample on treatment, and then follow the schedule outlined above.…”
Section: Discussionmentioning
confidence: 99%
“…A recent smaller study by Brown et al [11] found that delayed TSH suppression was significantly related to plasma T4 levels and dosage of L-T4, suggesting that it may be due to undertreatment. The authors recommended an initial starting dose of 50 µg/day of L-T4 for early TSH suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies including a randomised trial have recommended a higher initial dose of L-T4 to achieve more rapid TSH suppression [11, 24]. However, some authors have reported persistently raised TSH in infants in whom adequate L-T4 was given and whose plasma T4 levels were in the upper range of normal [8, 25, 26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations